Review of BIM-Based Software in Architectural Design: Graphisoft Archicad VS Autodesk Revit - Lambertus Waas; Enjellina (Journal of Artificial Intelligence in Architecture, 2022)
Revolution Industry 4.0 delivers impact on world development AEC (architect, engineering, and construction), especially in the development of useful digital technology for acceleration development infrastructure namely BIM ( Building Information Modeling ). BIM uses 3D software to support all potential and productivity in designing building construction. This article aims to review the advantages and limitations of the software Graphisoft Archicad and Autodesk Revit, especially in the field of BIM. the method used in writing an article is a review paper with a review of six journals and three expert opinions. The results of the review show that the Archicad software dominates the criteria for the field of work and 3D display. Temporary software Revit dominates in the field of work criteria in terms of the number of owned features because integrated by the developers of the Autodesk program. Archicad software is more compatible for users who want to have a more concise and easy-to-understand interface, while Revit software is more compatible for users with more complex project scales. Both of these software support parametric design. In Archicad and Revit Rhinoceros-grasshopper software can be used for Live Connection, but Archicad also has Param-O parametric object library and Revit has Dynamo for visual programming of parameter modeling. This shows that users should know more about their needs before choosing to use one of this BIM software.